Oestrogen promotes tumorigenesis of bladder cancer by inducing the enhancer RNA—eGREB1. Issue 12 (4th September 2018) - Ding, Mengting; Liu, Yuhan; Li, Jianfa; Yao, Lin; Liao, Xinhui; Xie, Haibiao; Yang, Kang; Zhou, Qun; Liu, Yuchen; Huang, Weiren; Cai, Zhiming
Abstract: In recent years, studies have shown that enhancer RNAs (eRNAs) can be transcribed from enhancers. Increasing evidence has revealed that eRNAs play critical roles in the development of various cancers. Oestrogen‐associated eRNAs are closely related to breast cancer. In view of the gender differences in bladder cancer (BCa), we suppose that oestrogen‐associated eRNAs are also involved in tumorigenesis of BCa. In our study, we first demonstrated that eGREB1 derived from the enhancer of an oestrogen‐responsive gene—GREB1 was up‐regulated in BCa tissues, and the expression level of eGREB1 is positively associated with the histological grade and TNM stage of BCa. Knockdown of eGREB1 by CRISPR‐Cas13a could inhibit cell proliferation, migration and invasion and induce apoptosis in BCa cells T24 and 5637. Besides, we exhibited the promoting effect of oestrogen on BCa cells. What's more, down‐regulation of eGREB1 could improve the malignant biological characteristics of BCa cells induced by oestrogen. In conclusion, our data indicated that eGREB1 plays oncogenic role and oestrogen may promote the occurrence and progression of BCa by inducing eGREB1 production. Our findings provide new insights into the prevention of BCa and develop a novel therapeutic target for the treatment of BCa.